Hydrodynamics of high-speed marine vehicles - Faltinsen, O. M. 1944- (Cambridge University Press, 2005)
Discusses the three main categories of high-speed marine vehicles - vessels supported by submerged hulls, air cushions or foils.
Keywords: Motorboats.; Ships -- Hydrodynamics.; Hydrodynamics.; Hydrofoil boats.; elektronické knihy; electronic books